Os limites da atuação da justiça constitucional no constitucionalismo contemporâneo - Souza, Léa Émile Maciel Jorge de (2013)
This study aims to analyze the changes that the so-called contemporary constitutionalism operated in the form of performance of constitutional justice. The concentrated constitutional jurisdiction inspired in Kelsen ideas, was designed on the basis of a single unique function: the exercise of judicial review in a monopolized form. The fact is that this constitutional jurisdiction was designed for a state that is based on a Constitution devoid of axiological load and it would just be the foundation of the legal validity. Today, most States have Constitutions that guarantee fundamental rights and guarantees and incorporate values through the principles, so the task of defending the Constitution of the Constitutional Court can not just be a task of negative legislator, when arise new regulations that directly offend the Constitution. The new configuration of Constitutional Law, in the context of contemporary constitutionalism, asks for a Constitutional Court to assist in the implementation of the Constitution in all its materiality. Thus, the figure of the Constitutional Court can not be identified with an autonomous agency with respect to the other powers that has one only duty: do the judicial review in a monopolized way. The need to guarantee the implementation of the Constitution in all its materiality made the Constitutional Court play another function beyond the judicial review (called structuring function), were aggregated other functions, such as interpretive and enunciation of constitutional laws; arbitration; legislation; governance; and "communitarian". However, such functions shall be performed within certain limits so that the Constitutional Court does not infringe the functional conformation imposed by the Constitution and in that way become possible a shared exercise of the constitutional implementation between all the organs of the State